Avoidable mortality in people with schizophrenia or bipolar disorder in England. - Hoang, U; Goldacre, M; Stewart, R (2013)
OBJECTIVE: To quantify the extent of 'avoidable mortality' in those with schizophrenia or bipolar disorder and to quantify the effect a reduction in these might have on the mortality gap associated with severe mental illness. METHOD: A cohort was studied of people aged <75 years, discharged from inpatient care with schizophrenia or bipolar disorder in 2006-2007, and followed up for 365 days. Standardised mortality ratios (SMRs) were calculated followed by hypothetical SMRs, estimating the residual mortality gap if 'avoidable' causes and suicide in the cohorts had occurred at the same level as those in the general population. RESULTS: Avoidable deaths comprised 60.2% and 59.2% of all deaths in the schizophrenia and bipolar disorder cohorts respectively. All-cause SMRs were 4.23 (95% CI 3.85-4.60) and 2.60 (2.21-3.00) respectively. After discounting the excess attributable to avoidable causes and suicide, the SMRs fell to 2.38 (2.09-2.66) and 1.66 (1.35-1.98) respectively. CONCLUSION: Bringing mortality from avoidable causes and suicide down to general population levels would reduce the overall mortality excess in severe mental illness substantially, by about 50%, but would not eliminate it. Other underlying factors beyond those conventionally considered as 'avoidable' need further research.